Kaji Eksperimen lengkungan Sudu Turbin Angin Savonius Tipe-U - Delffika Canra -; Meri Rahmi -; ikhsan - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
Wind energy sources in coastal areas of Indonesia are generally one of the potential renewable energy sources (renewable energy resources) that are abundant, environmentally friendly and renewable. Savonius wind turbines can produce relatively high torque even at low wind speeds. Because it is very well developed to produce electrical energy. To get a large amount of electrical power, a large turbine construction is also needed which also requires a large amount of money, of course. For this reason, the dimensions of this wind turbine construction need to be developed, known as aspect ratio (Ar). Ar which has been studied is the cross section of the blade, as well as other values. Whereas the arch depth or blade length of type U is still likely to be studied. Therefore it is necessary to do research on type U blade arcs to get more power than before. Experimental method by making a prototype savonius type U wind turbine with 2 blades. The parameters varied only in terms of the ratio of arc length and blade cross section, other parameters followed the previous study. The expected experimental results get the aspect ratio (Ar) of the best blade in capturing wind energy and producing large electrical power.